A metabolomics approach for examining synbiotic protection against infectious enteric pathogens - Nealon, Nora Jean, author; Ryan, Elizabeth P., advisor; Dean, Gregg, committee member; Henry, Charles, committee member; Tobet, Stuart, committee member (Colorado State University. Libraries, 2019)
Infectious gastrointestinal diseases contribute to billions of global cases of human illness annually. Salmonella enterica serovar Typhimurium and human rotavirus represent two human health challenges, where escalating multidrug resistance and poor vaccine efficacy warrant the development of alternative treatments. Health-promoting probiotic microorganisms are becoming increasingly studied for their production of bioactive small molecules that confer protective effects against enteric pathogens. Among probiotics, Lactobacilli, Bifidobacteria and E. coli Nissle form synbiotics with rice bran, the prebiotic-rich outer coating of brown rice, to enhance animal protection against S. Typhimurium infection and human rotavirus diarrhea compared to probiotics or rice bran alone. Despite these beneficial interactions of probiotics and rice bran, a knowledge gap exists in our understanding of the synbiotic small molecules driving these protective effects, especially across probiotic species differences in small molecule production. To test our overarching hypothesis that probiotic species would metabolize rice bran into distinct suites of small molecules that suppressed pathogen function, we first applied the cell-free supernatant from L. paracasei, L. fermentum, and L. rhamnosus cultured with rice bran to S. Typhimurium and observed magnitude-dependent growth suppression across synbiotics. Both L. paracasei and L. fermentum supernatants exhibited enhanced growth suppression compared to their probiotic-only treatments and contained differentially abundant antimicrobial lipids, amino acids, and nucleotides that have not been previously characterized for antimicrobial functions. The cell-free supernatant of the L. paracasei and L. fermentum synbiotics were fractionated and applied to S. Typhimurium to identify the small molecules driving their enhanced Salmonella growth suppression. Metabolite profiles were also compared across synbiotics. Each synbiotic produced several bioactive fractions that suppressed Salmonella growth. While both L. fermentum and L. paracasei bioactive fractions contained abundant lipids, L. fermentum fractions were selectively-enriched in the energy metabolite fumarate and L. paracasei fractions were uniquely-enriched with amino acids (imidazole lactate, ornithine) suggesting that Lactobacillus spp. probiotics could differentially metabolize rice bran to drive Salmonella growth suppression with different suites of small molecules. To examine probiotic metabolism of rice bran in mammalian systems, we compared the intestinal and blood metabolomes of healthy adult mice and gnotobiotic, neonatal pigs that were fed combinations of probiotics and rice bran to the metabolomes of animals consuming rice bran or probiotics alone. In mice, a notable difference following 15 weeks consumption of B. longum fermented was that the arginine metabolite N-delta-acetylornithine was significantly increased in B. longum fermented rice bran compared to rice bran alone and was elevated in both the colon tissue and blood of mice consuming fermented rice bran compared to rice bran alone. In gnotobiotic neonatal pigs, three weeks of prophylactic supplementation with E. coli Nissle and L. rhamnosus GG and rice bran were more effective at reducing human rotavirus diarrhea compared to pigs given these probiotics or rice bran alone. Approximately 300 colon and blood metabolites that were differentially-abundant between synbiotic-consuming pigs versus pigs consuming probiotics alone were identified, over 50% of which were lipids and amino acids. Similar modulations lipid and amino acid metabolites (sphingolipids, diacylglycerols, arginine metabolites) were identified in the colon tissue and blood of mice and pigs consuming the synbiotic treatments. Consequently, the association of these metabolite profiles with human rotavirus diarrhea protection, when combined with their presence in two mammalian models, provides strong rationale for these infectious enteric disease protective roles harbored by these metabolites. The results of these studies provide a role for synbiotics in the prevention of infectious gastrointestinal diseases. For the first time, high-throughput metabolomics analyses were applied to identify differential bioactive metabolite production by Lactobacillus spp. + rice bran synbiotics that suppressed S. Typhimurium growth, as well as to compare bioactive metabolites produced by B. longum, L. rhamnosus GG, and E. coli Nissle in mice and pigs that were protective against human rotavirus diarrhea. The contributions of amino acids and lipids to the enhanced capacities of these synbiotics compared to probiotics or rice bran alone can be studied further for their mechanisms of action on pathogens. Ultimately, these bioactive synbiotic metabolites can guide the optimization and development of broad-spectrum antimicrobials and other prophylactic agents that protect against infectious enteric diseases across the human and animal lifespan.
Keywords: metabolomics; probiotic; synbiotic; prebiotic; enteric disease; rice bran